2005
DOI: 10.1115/1.1839212
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tool–Sheet Interaction on Damage Evolution in Electromagnetic Forming of Aluminum Alloy Sheet

Abstract: A study of the effect of tool–sheet interaction on damage evolution in electromagnetic forming is presented. Free form and conical die experiments were carried out on 1 mm AA5754 sheet. Safe strains beyond the conventional forming limit diagram (FLD) were observed in a narrow region in the free form experiments, and over a significant region of the part in the conical die experiments. A parametric numerical study was undertaken, that showed that tool–sheet interaction had a significant effect on damage evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(41 citation statements)
references
References 19 publications
0
35
0
1
Order By: Relevance
“…In the past few decades, many scholars pay much attention to the formability and microstructure evolution of various materials when using electromagnetic forming (EMF). For example, Imbert et al [1] demonstrated increased formability in AA5754 sheet formed into a conical die using EMF technology. Li et al [2] found that the forming limit of Ti-6Al-4V is increased by 24.37 % in electromagnetic free bulging.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, many scholars pay much attention to the formability and microstructure evolution of various materials when using electromagnetic forming (EMF). For example, Imbert et al [1] demonstrated increased formability in AA5754 sheet formed into a conical die using EMF technology. Li et al [2] found that the forming limit of Ti-6Al-4V is increased by 24.37 % in electromagnetic free bulging.…”
Section: Introductionmentioning
confidence: 99%
“…Hu and Daehn, 1996;Mercier and Molinari, 2004), and contact effects are known to strongly influence high velocity forming (e.g. Balanethiram and Daehn, 1994;Imbert et al, 2005). Finally, the present work makes the implicit assumption that the thermal response of the material is the same under quasistatic and EMF forming speeds.…”
Section: Resultsmentioning
confidence: 97%
“…They found that substantially higher strains can be accomplished in the EHF process, comparison of the maximum strains NOMENCLATURE V = Forming velocity E = Discharge energy of system C = System capacitance U = Input voltage resulting from EHF into a conical die and a v-shape die with the maximum strains resulting from quasi-static LDH testing (limiting dome height). Imbert et al 7 illustrated increased formability in AA5754 sheet when formed into a conical die using electromagnetic forming technology. They utilized a damage-based material model to demonstrate that the tool-sheet interaction had a signicant effectin suppressing necking and damage evolution.…”
Section: Introductionmentioning
confidence: 98%